The socio-cultural factors behind the Saudi attitude toward COVID-19 vaccination: A survey-based study - Al-Ghuraibi, Muna; Dighriri, Ibrahim M.; Elrggal, Mahmoud Essam; Obaid, Najla A. (Frontiers in Public Health, 2023)
Introduction Vaccine distrust and rejection are thought to contribute to disease outbreaks and increased mortality. The present study aimed to analyze the socio-cultural characteristics and attitudes of the Saudi population toward vaccines, using a cross-sectional survey-based approach. Methods An online questionnaire was used, following the snowball method. A total of 444 people responded, of whom 333 (75%) were female, and 111 (25%) were male. Results The demographic characteristics associated with vaccine confidence were gender, job type, medical problems, and knowledge of coronavirus disease 2019 (COVID-19) symptoms. The hesitancy was highest (31.17%) among individuals aged 21–30 years old, and in more males (27.03%) expressed hesitancy than females (25.23%). However, if we focused on the percentage of the refusal to receive the vaccine, more females (15.23%) refused the vaccine than males (4.5%). More than one-third of the vaccine-hesitant respondents had limited knowledge of COVID-19 symptoms. Personal characteristics associated with vaccine confidence were described as the following: do not fully trust vaccines produced in a short time (42.1%), fear of the future results of the vaccine (30.4%), reluctance to allow a foreign material to enter the body (17.6%), no interaction with others, so no need for the vaccine (11.5%), low interaction with people (67.8%), and reluctance to make decisions (11.3%). The primary social motivation for getting the vaccine was to get back to normal life (67.6%). Discussion The results of the present study revealed that more than half of the respondents in Saudi Arabia were confident about the vaccine (61.7%), while only 25.7% were hesitant and 12.6% were unconvinced. Based on these results, in the early period of COVID-19 vaccine administration in the country (early 2021), before any governmental allowance and political intervention, we found that the socio-demographic and socio-cultural characteristics of the population were significant factors contributing to vaccination acceptance. Therefore, policymakers should support long-term safety studies of the vaccine, conduct educational programs giving high-priority to the populations' health, and tailor vaccination hesitancy reduction techniques to local communities.